THE INFLUENCE OF INVESTMENT KNOWLEDGE, SOCIODEMOGRAPHIC CHARACTERISTICS, AND RISK PROPENSITY ON SHARIA STOCK INVESTMENT DECISIONS - Carissa Nindya Nirwasita; Supriyanto Supriyanto (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of investment knowledge, sociodemographic characteristics, and risk propensity on investment decisions in Islamic stocks. The novelty of this research lies in integrating investment knowledge, sociodemographic characteristics, and risk propensity into a single analytical model, with a specific focus on Generation Z Muslim investors in the Solo Raya region within the context of sharia stock investment decisions. This study employs a quantitative approach. Primary data were collected through questionnaires distributed to 180 Generation Z Muslim investors in Solo Raya. Data analysis was conducted using SPSS version 25, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) test. The results indicate a positive and significant relationship between investment knowledge, sociodemographic characteristics, and risk propensity and investment decisions in Islamic stocks. These variables play a significant role in shaping investment decision-making among Generation Z Muslim investors. This study is limited to Generation Z Muslim investors in the Solo Raya region, so the findings cannot be broadly generalized. However, the results provide useful insights for practitioners and academics in understanding the factors that influence investment decisions in Islamic stocks.